UPAYA MENINGKATKAN KECERDASAN MUSIK MELALUI KEGIATAN BERNYANYI BERSAMA DI TK IT NURUL ILMI MEDAN - Pratiwi, Risa Ummah; Damanik, Maysarah Rabiul Aulia; Maimanah, Ashabul; Yunita, Zahra; Daulay, Mastianur; Marpaung, Zulham Efendi; Sit, Masganti (Al-ATHFAL: Jurnal Pendidikan Anak, 2023)
This research aims to find out how to increase musical intelligence through group singing activities at the IT Nurul Ilmi Kindergarten in Medan. This research uses a qualitative research type. The data collection techniques used were interviews, observation and documentation. The data analysis technique used is the Miles and Huberman model which includes four parts, namely data collection, data reduction, data presentation and verification or conclusions. The results of the research show that the stimulation of musical arts in singing activities provided by teachers for children aged 5-6 years is that teachers provide examples in groups, teachers provide opportunities for children, teachers stimulate with movement and songs, and teachers listen to songs to children